Protective Levels of Polysaccharide-Specific Maternal Antibodies May Enhance the Immune Response Elicited by Pneumococcal Conjugates in Neonatal and Infant Mice - Richter, Margret Y. (American Society for Microbiology, 2005)
Maternal antibodies (MatAbs) may protect the offspring against infections but may also interfere with their immune responses to vaccination. We have previously shown that maternal immunization with pneumococcal polysaccharides (PPS) conjugated to tetanus protein (Pnc-TT) protected the offspring against infections caused by three important pediatric serotypes. To study the influence of MatAb on the immune response to Pnc-TT early in life, adult female mice were immunized twice with Pnc-TT of serotype 1 (Pnc1-TT), and their offspring received Pnc1-TT subcutaneously three times at 3-week intervals starting at 1 week (neonatal) or 3 weeks (infant) of age. High levels of PPS-1-specific MatAb (>3 log) in offspring of Pnc1-TT-immunized dams completely inhibited their anti-PPS-1 response elicited by Pnc1-TT. In contrast, low or moderate (∼1 to 2 log) levels of MatAb did not interfere with and even enhanced the immune response of the offspring, and a booster response to a second Pnc1-TT dose was observed. Carrier-specific MatAbs had little effect on the response of offspring to the conjugate. All Pnc1-TT-immunized offspring were protected against pneumococcal bacteremia and had reduced lung infection. These results demonstrate that in the presence of MatAb, Pnc1-TT may elicit a protective PPS-1-specific antibody response and prime for PPS-1-specific memory in young offspring. Importantly, low or moderate levels of PPS-1-specific MatAb not only provided protection against pneumococcal infections but also enhanced the immune response elicited by Pnc1-TT in neonatal and infant mice. This murine model will be used to develop novel strategies combining maternal and neonatal immunization to protect against infections caused by encapsulated bacteria in early life.